Impact of Diabetes Mellitus Duration on Most Common Kidney Diseases: Dampak Durasi Diabetes Melitus pada Penyakit Ginjal yang Paling Umum - Hamid, Samahir Sabri (Universitas Muhammadiyah Sidoarjo, 2024)
Patients who were admitted to several hospitals in the city of Basrah were the subjects of the current study. The study aims to ascertain whether there is a correlation between the occurrence of renal disease and the moment at which type 1 and type 2 diabetes begin. The results of the questionnaire, which was completed by 70 males and females from rural and urban areas, ranging in age from 14 to 80 years, indicated a significant correlation between kidney disease onset and diabetes, with 55.4% of affected patients having type 1 diabetes before type 1 KD and 53.3% having type 2. Age and KD were also significantly correlated at the 0.01 level, as were diabetes type 1 and type 2 (0.777 and 0.795). Highlights: Study: Examined 70 diabetic patients in Basrah hospitals for kidney disease. Findings: 55.4% with type 1 and 53.3% with type 2 developed KD. Correlation: Diabetes, kidney disease, and age showed significant links (p < 0.01). Keywords: Diabetes, Kidney Disease, Correlation, Basrah, Epidemiology